Large Periglacial Lakes on the Spitsbergen (Svalbard): State in 2008–2012 and Dynamics in 1991–2022 - R. A. Chernov; K. V. Romashova (Лëд и снег, 2024)
Approximately 3,790 lakes of various genesis existed in the Svalbard archipelago in 2008–2012, the total area of which reached 395 km2. Among them, periglacial lakes were new objects which had been formed since the beginning of the 20th century due to the deglaciation of the archipelago. We found 554 glacial lakes which areas exceeded 0.01 km2. The total area of these lakes amounted to about a half of the area of all the lakes in the archipelago – 185 km2, and two thirds of this value were large glacial lakes. The paper presents the spatial distribution of large periglacial lakes and variability of them caused by the climate warming in the archipelago. At present, there are 35 periglacial lakes (over 1 km2 in size); all of them are in contact with glaciers and the greater part of them are dammed by the terminal moraines or by a glacier itself. According to the cartographic data of the Norwegian Polar Institute and satellite images, the areas of large lakes were determined successively in 1991, 2002, 2012, and 2022. For the period from 1991 to 2012, there was a twofold increase in their area from 24.4 to 53.7 km2, but in 2012–2022 this process slowed down. On the east of the archipelago, where the inland ice is widespread, the process of the lake formation is much slower. It had been noted that on the west all large glacial lakes were formed after 1936 due to active retreat of the glaciers. At the same time, both on the north and east, most of the large glacial lakes existed prior to 1936. During the periods under consideration, changes in the areas of individual objects reached multiple values. The most large-scale changes in the lake areas were associated with the ablation of glacial fronts in contact with the lake, a glacier surge, and outbursts of a few dammed lakes. Six lakes were identified, where the water level drop reached tens of meters. Despite the slowdown in the formation of lakes in the last decade, the enlargement of lakes continues. Relative increase in the total area of the large periglacial lakes over the past 30 years on the west and east of the archipelago is in direct proportion to decreasing in glaciation of these regions. Thus, the process of formation of large periglacial lakes may be used as an indicator of climate change in the archipelago.